2004
DOI: 10.1016/j.ehj.2004.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of left ventricular remodelling after myocardial infarction, assessed by transthoracic 3D echocardiography

Abstract: Three-dimensional echocardiography can differentiate patients with and without subsequent development of LV remodelling accurately and early on the basis of the 3D sphericity index, a new and highly predictive variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(122 citation statements)
references
References 26 publications
9
106
0
7
Order By: Relevance
“…The moderate (MOD) remodeling phenotype was defined as a LVEDV and/or LVESV that was >20% higher than the average value in sham. We used the 20% cutoff change in volume as a marker of more significant remodeling as previously described 14, 15…”
Section: Methodsmentioning
confidence: 99%
“…The moderate (MOD) remodeling phenotype was defined as a LVEDV and/or LVESV that was >20% higher than the average value in sham. We used the 20% cutoff change in volume as a marker of more significant remodeling as previously described 14, 15…”
Section: Methodsmentioning
confidence: 99%
“…Improvement of LV function occurred due to the contraction of the inferior region. The sphericity index was shown as an accurate predictor of LV remodelling in patients after an acute myocardial infarction (9). Studies have shown that Simpson's biplane calculation of EF can vary up to 4.1% between clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Мно-го работ отечественных и зарубежных авторов посвя-щено исследованию таких эхокардиографических па-раметров, как индексы сферичности, индекс напря-жения миокарда, индексы ремоделирования, мио-кардиальный стресс левого желудочка, маркёры диа-столической дисфункции. Считается, что некоторые из этих показателей являются более информативными, чем фракция выброса, размеры и объёмы ЛЖ при оценке тяжести ХСН [5].…”
Section: Discussionunclassified
“…Для оценки ремоделирования сердца при ХСН в по-следнее время стали использоваться такие показатели, как индексы сферичности, миокардиальный стресс, ин- [5], было показано, что индекс сферичности в большей степени, чем фракция выброса, коррелирует с клиническими проявлениями.…”
unclassified